Alice Zeniter ou l’art du renouveau - Pawlicki, Jędrzej (Studia Romanica Posnaniensia, 2018)
L’Art de perdre (Flammarion, 2017) is the fifth and latest novel of Alice Zeniter, French novelist and dramatist. She published her first novel at the age of sixteen. In this paper I will present L’Art de perdre as a novel related to the common history of France and Algeria. My main goal is to analyze the issues of memory according to the concepts of postmemory by Marianne Hirsch and archaeological novel by Dominique Viart. The article aims also at following a comparative study of L’Art de perdre and previous novels by Alice Zeniter: Jusque dans nos bras and Juste avant l’Oubli.